Irish house price indices ? methodological issues - Conniffe, Denis; Duffy, David (Economic & Social Studies, 1999)
This paper reviews the international literature on house price indices, looking at the basic methodologies employed, the variables chosen for the indices and the functional forms used. Ideas are sought for future improvements to an Irish index and tentative assessments are made of how Irish results correspond to published research findings. Although the recent vintage of hedonic house price indices in Ireland warrants caution in reaching conclusions, there are interesting correspondences with published results. Some issues are identified that will require resolution to achieve further progress.
Keywords: House prices; Housing market; Ireland; Quantitative methods; Price indices